UV-Vis spectroscopy and chemometric: a simple method to differentiate honey, partially ripe honey and nectars - Maldonado, Luis Maria; Marcinkevicius, Karenina; Alvarez, Alejandro Raul; Salomon, Virginia María; Gaggiotti, Monica Del Carmen; Messina, Natalia; Palacio, María Alejandra; Medina, S.; Maldonado, Mario Miguel; Orellano, Emanuel; Bedascarrasbure, Enrique Luciano (Ediciones INTA, 2024)
Honey is a supersaturated solution of sugars that also contains small amounts of enzymes, vitamins, phenolic compounds (e.g., flavonoids), terpenes, organic acids and hydrogen peroxide. The presence of such substances explains honey’s biological activity and absorbance of ultraviolet radiation. Honey is one of the three most adulterated foods worldwide. High-complexity and sensitivity techniques are used to detect such adulterations, like isotopic analysis and Nuclear Magnetic Resonance. However, a simpler, high-speed, low cost and more accessible analytical method would be more convenient to perform food analyses, particularly for bee products. In this regard, UV-Vis spectroscopy coupled with chemometric analysis has been widely and successfully used to analyze bee products. Therefore, this study aims to validate a methodology based on the use of UV-Vis spectroscopy coupled with chemometric analysis to differentiate the nectar recently collected by bees from partially mature honey and honey. Samples of different geographical and botanical origins were collected from two locations in Argentina; one trial was carried out in Tucumán (in the main lemon flow) and the other in Entre Ríos (eucalyptus flowering). Spectra between 190 nm and 420 nm were recorded and different projection methods were applied, including principal component analysis, FreeViz, and linear discriminant analysis. From the results, it is concluded that UV-Vis spectroscopy coupled with chemometric analysis allows differentiating recently collected nectar from partially mature honey and honey and that phenolic compounds are highly present in mature honey, which could favourably affect its biological activity.